2002
DOI: 10.1348/026151002166442
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of bullying, dominance, and victimization during the transition from primary school through secondary school

Abstract: Bullying and victimization were studied from a longitudinal, multi‐method, multi‐agent perspective as youngsters made the transition from primary through middle school. Generally, bullying and aggression increased with the transition to middle school and then declined. Bullying mediated youngsters' dominance status during the transition. Bullying may be one way in which young adolescents manage peer and dominance relationships as they make the transition into new social groups. Victimization declined from prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
656
4
49

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 859 publications
(778 citation statements)
references
References 44 publications
69
656
4
49
Order By: Relevance
“…Examination of the configural invariance model indicated that the factor mean for boys was greater than for girls. This is consistent with the literature indicating that in general, boys seem to experience more victimization and bullying than girls, up to an effect size of 0.50 Pellegrini & Long, 2002). Scalar invariance was then examined by constraining both factor and parameter means to zero to determine whether individual parameters differed significantly between the two groups and contributed to the decrease in fit in the metric invariance model.…”
Section: Factor Analysis Of Victimization Itemssupporting
confidence: 81%
See 1 more Smart Citation
“…Examination of the configural invariance model indicated that the factor mean for boys was greater than for girls. This is consistent with the literature indicating that in general, boys seem to experience more victimization and bullying than girls, up to an effect size of 0.50 Pellegrini & Long, 2002). Scalar invariance was then examined by constraining both factor and parameter means to zero to determine whether individual parameters differed significantly between the two groups and contributed to the decrease in fit in the metric invariance model.…”
Section: Factor Analysis Of Victimization Itemssupporting
confidence: 81%
“…The fact that the factor means confirmed the prior-established pattern in the literature of increased victimization experiences for boys than for girls Pellegrini & Long, 2002) and that the indicator means matched a pattern established in the literature of increased victimization experiences related to gender for girls than the boys (Lipson, 2001;Pellegrini, 2001;Schnoll et al, 2015;Shute et al, 2008), allowed us to conclude that continued analysis using this one-factor structure was appropriate.…”
Section: Factor Analysis Of Victimization Itemssupporting
confidence: 71%
“…Many children in the present study associate bullying with struggling for status, power, or friends (for an interesting study on bullying within friendships, see Mishna, Weiner, & Pepler, 2008). This social representation on bullying causes resembles the social dominance theory, which suggests that prosocial behavior as well as aggressive strategies such as bullying are used among children and adolescents to achieve and maintain social status and dominance (Pellegrini & Long, 2004;Walcott, Upton, Bolen, & Brown, 2008).…”
Section: Discussionmentioning
confidence: 56%
“…Pellegrini & Long, 2002). Students have to adapt to a new Bullying and Cyberbullying 10 10 environment and re-establish their social relationships.…”
Section: Bullying and Cyberbullying 8mentioning
confidence: 99%